Effects of Strength vs. Ballistic-Power Training on Throwing Performance. - Zaras, Nikolaos; Spengos, Konstantinos; Methenitis, Spyridon; Papadopoulos, Constantinos; Karampatsos, Giorgos; Georgiadis, Giorgos; Stasinaki, Aggeliki; Manta, Panagiota; Terzis, Gerasimos (J Sports Sci Med, 2013)
The purpose of the present study was to investigate the effects of 6 weeks strength vs. ballistic-power (Power) training on shot put throwing performance in novice throwers. Seventeen novice male shot-put throwers were divided into Strength (N = 9) and Power (n = 8) groups. The following measurements were performed before and after the training period: shot put throws, jumping performance (CMJ), Wingate anaerobic performance, 1RM strength, ballistic throws and evaluation of architectural and morphological characteristics of vastus lateralis. Throwing performance increased significantly but similarly after Strength and Power training (7.0-13.5% vs. 6.0-11.5%, respectively). Muscular strength in leg press increased more after Strength than after Power training (43% vs. 21%, respectively), while Power training induced an 8.5% increase in CMJ performance and 9.0 - 25.8% in ballistic throws. Peak power during the Wingate test increased similarly after Strength and Power training. Muscle thickness increased only after Strength training (10%, p < 0.05). Muscle fibre Cross Sectional Area (fCSA) increased in all fibre types after Strength training by 19-26% (p < 0.05), while only type IIx fibres hypertrophied significantly after Power training. Type IIx fibres (%) decreased after Strength but not after Power training. These results suggest that shot put throwing performance can be increased similarly after six weeks of either strength or ballistic power training in novice throwers, but with dissimilar muscular adaptations. Key pointsBallistic-power training with 30% of 1RM is equally effective in increasing shot put performance as strength training, in novice throwers, during a short training cycle of six weeks.In novice shot putters with relatively low initial muscle strength/mass, short-term strength training might be more important since it can increase both muscle strength and shot put performance.The ballistic type of power training resulted in a significant increase of the mass of type IIx muscle fibres and no change in their proportion. Thus, this type of training might be used effectively during the last weeks before competition, when the strength training load is usually reduced, in order to increase muscle power and shot put performance in novice shot putters.